International financial markets: Control or liberalization? - Gerhard Maier (Intereconomics, 1990)
Exchange rates, interest rates and share prices are subject—at least occasionally—to great fluctuations. Diverse economists regard the volatility of international financial markets as a threat to the goods and labour markets. They blame the price turbulences on the speculative behaviour of a large section of market participants, and claim that the deregulation and liberalization of the international financial markets in the eighties has therefore already gone too far. Under discussion today are approaches to a re-regulation of the money, capital and foreign exchange markets. These proposals are evaluated in the following paper.
Keywords: 330; Capital Markets